Analysis of the Application of the Capital Asset Pricing Model (CAPM) Method to Final Decision in Share Investment - Nuralista Prihastiwi (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
Investment is delaying or reducing consumption at present in order to get benefits in the future. This activity requires a significant investment (long-term financing). Before making an investment decision, investors must conduct a review first. The benefits of this research are not only for making a decision on several investment instruments, but also related to company assets. Given the increasing interest of investors in investing, to avoid investment failure it is necessary to conduct research on investment decisions through the 'capital price model and rate of change in the method of return. Therefore, researchers took the initiative to conduct the same research. The reason for choosing shares listed on the LQ45 index is because the stocks listed in the LQ45 index are stocks that have high liquidity on the Indonesia Stock Exchange (IDX). In other words, shares listed on the LQ45 index are stocks that are actively traded on the stock market. Of course, this determines potential investors because these shares are active stocks. From this research, there are 3 undevalued stocks from 5 samples that are worth buying by investors.